Eksplorasi Unsur Arsitektur Bajo pada Kapal Thousand Sunny dalam Serial Anime One Piece sebagai Representasi Kekayaan Citra Budaya - Ahsan Hidayat Setiadi; Andi Almustagfir Syah; Muhammad Muhsar (Syntax Idea)
The Thousand Sunny ship in the anime "One Piece" is not just a means of transportation but also a rich cultural symbol. In this study, we explore the elements of underwater architecture on this ship to reflect the cultural richness of the anime. We found that the underwater architecture on the Thousand Sunny is not only part of the visual design but also represents the history, cultural values, and unique aesthetics in the world of "One Piece." This research fills a gap in understanding how these elements are represented and how they function as a cultural mirror in this anime. Using a multidisciplinary approach, we connect the concept of cultural representation in popular media, architectural aesthetics, and the interaction between art and cultural identity to explain the relevance of underwater architecture elements in the "One Piece" narrative to popular culture. The results of this research are expected to provide new insights into the role of architecture in popular culture and reveal the richness of cultural imagery in the underwater architecture elements on the Thousand Sunny.